(untitled) (Hoboken, 2005)
Leading experts in water-related fields have come together to make Water Encyclopedia a one-stop, comprehensive reference about the world s most important natural resource. It covers designated topics in a clear concise and authoritative manner. The treatment is practical in orientation, keeping in mind the needs of the users. Theory is included only where required for an understanding of the topic.
Keywords: Water,Water quality,Water resources development; Supply